Soil aggregates by design: Manufactured aggregates with defined microbial composition for interrogating microbial activities in soil microhabitats. (September 2020) - Harvey, Harry J.; Wildman, Ricky D.; Mooney, Sacha J.; Avery, Simon V.
Abstract: Differences in the structure of microbial communities are reported to exist between the inside and outside of soil aggregates, but the impacts of soil aggregation on microbial activity in soils, essential for soil health, have proven difficult to study in a controlled manner. We have developed a new method to manufacture soil macroaggregates in the laboratory with the ability to introduce microorganisms of choice to the endo- or exo-aggregate environments, offering new avenues for experimental research. X-ray Computed Tomography imaging confirmed the manufactured aggregates had similar overall porosity, pore size and pore connectivity to naturally-formed aggregates. We exploited this new approach to test the hypothesis that microorganisms within aggregates are protected from environmental stresses, in comparison to organisms located near aggregate surfaces. Soil isolates of yeasts introduced to the interior or exterior of manufactured soil aggregates showed no significant difference in the survival of metal- or anoxic-stresses, but organisms within aggregates were protected from heat stress in a time-dependent manner. The results indicate that microbial communities may be protected from particular environmental perturbations by the complex porous architecture that arises from the aggregated soil structure, and underscore the value of this new approach for improving our understanding of the interactions between the soil physical environment and the associated soil biology. Graphical abstract: Image 1 Highlights: A method for manufacturing soil aggregates that mirror natural counterparts. Production of soil aggregates with defined microbial compositions and structure. Differential stress response of microorganisms within or outside soil aggregates. Stressor- and time-dependence of insulation from stress within soil aggregates.